Viral Mimetic-Induced Inflammation Abolishes Q-Pathway, but Not S-Pathway, Respiratory Motor Plasticity in Adult Rats - Hocker, Austin D.; Huxtable, Adrianne G. (Frontiers in Physiology, 2019)
Inflammation arises from diverse stimuli eliciting distinct inflammatory profiles, yet little is known about the effects of different inflammatory stimuli on respiratory motor plasticity. Respiratory motor plasticity is a key feature of the neural control of breathing and commonly studied in the form of phrenic long-term facilitation (pLTF). At least two distinct pathways can evoke pLTF with differential sensitivities to bacterial-induced inflammation. The Q-pathway is abolished by bacterial-induced inflammation, while the S-pathway is inflammation-resistant. Since viral-induced inflammation is common and elicits distinct temporal inflammatory gene profiles compared to bacterial inflammation, we tested the hypothesis that inflammation induced by a viral mimetic (polyinosinic:polycitidylic acid, polyIC) would abolish Q-pathway-evoked pLTF, but not S-pathway-evoked pLTF. Further, we hypothesized Q-pathway impairment would occur later relative to bacterial-induced inflammation. PolyIC (750 µg/kg, i.p.) transiently increased inflammatory genes in the cervical spinal cord (3 hours), but did not alter medullary and splenic inflammatory gene expression, suggesting region specific inflammation after polyIC. Dose-response experiments revealed 750 µg/kg polyIC (i.p.) was sufficient to abolish Q-pathway-evoked pLTF at 24 hours (17 ± 15% change from baseline, n = 5, p > 0.05). However, polyIC (750 µg/kg, i.p.) at 3 hours was not sufficient to abolish Q-pathway-evoked pLTF (67 ± 21%, n = 5, p < 0.0001), suggesting a unique temporal impairment of pLTF after viral-mimetic-induced systemic inflammation. A non-steroidal anti-inflammatory (ketoprofen, 12.5 mg/kg, i.p., 3 hours) restored Q-pathway-evoked pLTF (64 ± 24%, n = 5, p < 0.0001), confirming the role of inflammatory signaling in pLTF impairment. On the contrary, S-pathway-evoked pLTF was unaffected by polyIC-induced inflammation (750 µg/kg, i.p., 24 hours; 72 ± 25%, n = 5, p < 0.0001) and was not different from saline controls (65 ± 32%, n = 4, p = 0.6291). Thus, the inflammatory-impairment of Q-pathway-evoked pLTF is generalizable between distinct inflammatory stimuli, but differs temporally. On the contrary, S-pathway-evoked pLTF is inflammation-resistant. Therefore, in situations where respiratory motor plasticity may be used as a tool to improve motor function, strategies targeting S-pathway-evoked plasticity may facilitate therapeutic outcomes.